(untitled) (Asian Journal of Agriculture, 2021)
Abstract. Li S, Bitsch L, Hanf JH. 2021. Grape supply chain: Vertical coordination in Ningxia, China. Asian J Agric 5: 12-21. Since 2018, China has been the second-largest grape-growing country in the world, with 875 thousand hectares in total. A former study indicated a transformation within the wine grape supply chain management in the Chinese wine market, from traditional coordination to significant vertical integration. The Ningxia Helan Mountain’s Eastern Foothill wine region (China) is considered to be the best wine region in China and has potential to lead domestic wine production. This study summarizes the typology of grape supply models in the Ningxia wine industry. We also examine influencing factors for the arrangements of current vertical coordination models of grape materials supply, particularly the hybrid organizations and contractual relationships are analyzed.